The Diavik Waste Rock Project: Geochemical and microbiological characterization of low sulfide content large-scale waste rock test piles. (February 2016) - Bailey, Brenda L.; Blowes, David W.; Smith, Leslie; Sego, David C.
Abstract: Two experimental waste-rock piles (test piles), each 15 m in height × 60 m × 50 m, were constructed at the Diavik diamond mine in Northern Canada to study the behavior of low-sulfide content waste rock, with a similarly low acid-neutralization potential, in a continuous permafrost region. One test pile with an average of 0.035 wt.% S (<50 mm fraction; referred to as Type I) and a second test pile with an average of 0.053 wt.% S (<50 mm fraction; referred to as Type III) were constructed in 2006. The average carbon content in the <50 mm fraction of waste rock in the Type I test pile was 0.031 wt.% as C and in the Type III test pile was 0.030 wt.% as C. The NP:AP ratio, based on the arithmetic mean of particle-size weighted NP and AP values, for the Type I test pile was 12.2, suggesting this test pile was non-acid generating and for the Type III test pile was 2.2, suggesting an uncertain acid-generating potential. The Type I test pile maintained near-neutral pH for the 4-year duration of the study. Sulfate and dissolved metal concentrations were low, with the exception of Ni, Zn, Cd, and Co in the fourth year following construction. The pore water in the Type III test pile contained higher concentrations of SO4 2− and dissolved metals, with a decrease in pH to <4.7 and an annual depletion of alkalinity. Maximum concentrations of dissolved metals (20 mg L −1 Ni, 2.3 mg L −1 Cu, 3.7 mg L −1 Zn, 35 μg L − 1 Cd, and 3.8 mg L −1 Co) corresponded to decreases in flow rate, which were observed at the end of each field season when the contribution of the total outflow from the central portion of the test pile was greatest. Bacteria were present each year in spite of annual freeze/thaw cycles. The microbial community within the Type I test pile included a population of neutrophilic S-oxidizing bacteria. Each year, changes in the water quality of the Type III test-pile effluent were accompanied by changes in the microbial populations. Populations of acidophilic S-oxidizing bacteria and Fe-oxidizing bacteria became more abundant as the pH decreased and internal test pile temperatures increased. Irrespective of the cold-climate conditions and low S content of the waste rock, the geochemical and microbiological results of this study are consistent with other acid mine drainage studies; indicating that a series of mineral dissolution–precipitation reactions controls pH and metal mobility, and transport is controlled by matrix-dominated flow and internal temperatures. Highlights: Effluent from low S content (<0.1 wt.% S) waste rock had low pH (pH < 4.5), and high concentrations of SO4 (maximum of 2800 mg L −1 ) and dissolved metals. Water quality varied with seasonal temperatures and sulfide-mineral oxidation rates. Mineral dissolution–precipitation reactions controlled pH and metal mobility. Solutes migrated downwards through matrix dominated flow.